Integración de los mercados laborales en América del norte - Ruiz Durán, Clemente (Cuadernos de Relaciones Laborales, 2006)
This report is a revision on North American (Canada, EE.UU and Mexico) economies from the perspective of the regional integration and the Free Trade Agreement (TLC) during the last ten years. In the study that the author carries on, it is emphasized the unequal distribution of the incomes in this American area, the achievements and the consequences of the integration, as well as the effects of these issues on the labour relationships. Besides, it is emphasized the outstanding role that the migratory role has in Mexico and the United States, principally. Lastly, the study, takes into account the new labour worlds, emphasizing the employability and the structural and organizer changes that are taking place in this area.